2021
DOI: 10.1021/acs.est.1c03314
|View full text |Cite
|
Sign up to set email alerts
|

Europe-Wide Atmospheric Radionuclide Dispersion by Unprecedented Wildfires in the Chernobyl Exclusion Zone, April 2020

Abstract: From early April 2020, wildfires raged in the highly contaminated areas around the Chernobyl nuclear power plant (CNPP), Ukraine. For about 4 weeks, the fires spread around and into the Chernobyl exclusion zone (CEZ) and came within a few kilometers of both the CNPP and radioactive waste storage facilities. Wildfires occurred on several occasions throughout the month of April. They were extinguished, but weather conditions and the spread of fires by airborne embers and smoldering fires led to new fires startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…For weapons- 137 Cs, the cessation of atmospheric tests resulted in no noteworthy new weapons- 137 Cs fallout after the last test in 1980. Nowadays, the baseline of airborne 137 Cs (<10 μBq·m –3 in Germany) contributes insignificantly to the relatively high inventory in soil , and consequently in wild boars. Considering that the above-mentioned contamination level is orders of magnitude greater than the 137 Cs inventories reported in less contaminated regions, , it suggests a substantial impact of Chornobyl- 137 Cs on the Bavarian ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…For weapons- 137 Cs, the cessation of atmospheric tests resulted in no noteworthy new weapons- 137 Cs fallout after the last test in 1980. Nowadays, the baseline of airborne 137 Cs (<10 μBq·m –3 in Germany) contributes insignificantly to the relatively high inventory in soil , and consequently in wild boars. Considering that the above-mentioned contamination level is orders of magnitude greater than the 137 Cs inventories reported in less contaminated regions, , it suggests a substantial impact of Chornobyl- 137 Cs on the Bavarian ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…This affects the extent to which findings are generalizable. Wildfires also occurred elsewhere during this period including Siberia [2], Ukraine [55], the Brazilian Pantanal [56], China [57,58], Indonesia [59], India [60], Colombia [61], and across the Mediterranean [62]. Further research is warranted into how these wildfires converged with the COVID-19 pandemic in these localities (i.e.…”
Section: Limited Geographies Studiedmentioning
confidence: 99%
“…Direct exposure to harmful wildfire smoke is much more far-ranging than indicated by the studies identified in this review. For example, radioactive smoke from the 2020 wildfires in the Chernobyl Exclusion Zone in Ukraine was detected in Western Europe [55]. Harmful smoke from the 2021 Bootleg fire in the western United States traveled across the continent [63,64].…”
Section: Limited Geographies Studiedmentioning
confidence: 99%
“…The approach consists in the minimization of a cost function which measures the mismatch between modelled and observed 134 Cs air concentration. Regularization techniques are applied to ensure the existence and the unicity of the solution [3]. Then, for each optimal inverted source related to each grid point, the agreement between modelled and observed air concentration measurements is assessed using the factor 5 indicator (FAC5).…”
Section: Release Location and Magnitudementioning
confidence: 99%